YENİ TASARLANAN HAVALI KOLLEKTÖRLER YARDIMI İLE REYHAN VE NANE KURUTULMASI - GÜLÇİMEN, FEVZİ (Fırat Üniveristesi, 2008)
Bu çalışmada, yeni geliştirilen havalı güneş kolektörleri kullanılarak reyhan ve nane kurutulması sağlanmış ve kurutma parametreleri deneysel ve teorik olarak araştırılmıştır. Çeşitli yüzey profillerine sahip havalı güneş kolektörleri, hava sirkülasyonu sağlayan radyal fan ve kurutma odasından oluşan, deney düzeneği kurulmuş ve deneyler yapılmıştır. Kurutma deneylerinde nane ve reyhana uygun kurutma sıcaklıkları seçilmiş ve farklı debilerde deneyler gerçekleştirilmiştir. Deney sonuçlarından yararlanarak, nane ve reyhan için ayrı ayrı deneysel bağıntılar elde edilmiş. Elde edilen deneysel bağıntılar literatür ile karşılaştırılmıştır. Ayrıca nane ve reyhan kurutulması için matematik modelleme geliştirilmiştir.

In this study, drying parameters of mint and sweet basil were investigated as experimental and theoretical using solar drying system. A forced convection solar dryer system consisting of new designed solar air collectors with different surface profiles, a circulation fun and a drying cabinet are used for the experiments. The drying experiments were conducted at different air mass flow rates at the selected appropriate drying temperatures of mint and sweet basil. For the drying data obtained by experimental results of mind and sweet basil, new mathematical drying model which was developed as a function of none dimension numbers, was compared with ten different drying models in the literature. It was shown that the results were in good agrement.
Drying of the mint and sweet basil with new designed air collectors and determining of the drying parameters
Keywords: Teknik Eğitim